Renal Manifestations of IgG4-Related Disease: A Concise Review - Shahrukh T. Towheed; Wayel Zanjir; Kevin Yi Mi Ren; Jocelyn Garland; Marie Clements-Baker (International Journal of Nephrology)
IgG4-related disease (IgG4-RD) is an immune-mediated disorder marked by fibro-inflammatory masses that can infiltrate multiple organ systems. Due to its relatively recent discovery and limited understanding of its pathophysiology, IgG4-related disease may be difficult to recognize and is consequently potentially underdiagnosed. Renal involvement is becoming regarded as one of the key features of this disease. To date, the most well-recognized renal complication of IgG4-related disease is tubulointerstitial nephritis, but membranous glomerulonephritis, renal masses, and retroperitoneal fibrosis have also been reported. This concise review has two objectives. First, it will briefly encapsulate the history, epidemiology, and presentation of IgG4-related disease. Second, it will examine the reported renal manifestations of IgG4-related disease, exploring the relevant histology, imaging, clinical features, and treatment considerations. This synthesis will be highly relevant for nephrologists, rheumatologists, general internists, and renal pathologists to raise awareness and help improve early recognition of IgG4-related kidney disease (IgG4-RKD).